Financial accounting theory and standards - Harvey, Mike.; Keer, Fred. (Great Britain : MHL Typesetting Ltd, 1983)
The book retains its overall objective of explaining accounting theory and demonstrating its relevance to practitioners, there is now a firm link between that theory and the statements of standard accounting practice. This second edition has succeeded in its aim of illustrating the obvious links between accounting theory and the SSAPs and , in so doing, has enhanced its attractiveness as an examination book.
"Still invaluable to any accountant who wonders what all the fuss is about over standards. The book will be particularly useful to students."
Includes bibliographical references and index.
hza 07/09/2018
Loans
Keywords: Accounting